CSN-CRL Complexes: New Regulators of Adipogenesis - Dawadschargal Dubiel; Michael Naumann; Wolfgang Dubiel (Biomolecules)
Recent discoveries revealed mechanistic insights into the control of adipogenesis by the Constitutive Photomorphogenesis 9 Signalosome (CSN) and its variants, CSNCSN7A and CSNCSN7B, which differ in the paralog subunits, CSN7A and CSN7B. CSNCSN7A and CSNCSN7B variants form permanent complexes with cullin-RING-ubiquitin ligases 3 and 4A (CRL3 and CRL4A), respectively. These complexes can be found in most eukaryotic cells and represent a critical reservoir for cellular functions. In an early stage of adipogenesis, mitotic clonal expansion (MCE), CSN-CRL1, and CSNCSN7B-CRL4A are blocked to ubiquitinate the cell cycle inhibitor p27KIP, leading to cell cycle arrest. In addition, in MCE CSN-CRL complexes rearrange the cytoskeleton for adipogenic differentiation and CRL3KEAP1 ubiquitylates the inhibitor of adipogenesis C/EBP homologous protein (CHOP) for degradation by the 26S proteasome, an adipogenesis-specific proteolysis. During terminal adipocyte differentiation, the CSNCSN7A-CRL3 complex is recruited to a lipid droplet (LD) membrane by RAB18. Currently, the configuration of the substrate receptors of CSNCSN7A-CRL3 on LDs is unclear. CSNCSN7A-CRL3 is activated by neddylation on the LD membrane, an essential adipogenic step. Damage to CSN/CUL3/CUL4A genes is associated with diverse diseases, including obesity. Due to the tremendous impact of CSN-CRLs on adipogenesis, we need strategies for adequate treatment in the event of malfunctions.